2014
DOI: 10.1007/s10900-014-9878-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Profile of Ophthalmic Disorders in Oculocutaneous Albinism: A Field Report from South-Eastern Nigeria

Abstract: To assess the burden and spectrum of refractive and non-refractive ophthalmic disorders in south-eastern Nigerians with oculocutaneous albinism. In a population-based survey in Enugu state, between August, 2011 and January, 2012, albinos were identified using the database of the Enugu state's Albino Foundation, and mass media-based mobilisation. The participants were enrolled at the Eye Clinics of the University of Nigeria Teaching Hospital and Enugu State University of Science and Technology Teaching Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 23 publications
2
15
2
Order By: Relevance
“…It has been postulated that the subnormal presenting visual acuity may be due to delayed visual maturation, foveal hypoplasia, nystagmus, strabismus and iris trans-illumination. Udeh., et al reported similar posterior segment finding in their study at Enugu, Nigeria [11]. Other studies in Nepal and the USA also had similar results [17,21,22].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…It has been postulated that the subnormal presenting visual acuity may be due to delayed visual maturation, foveal hypoplasia, nystagmus, strabismus and iris trans-illumination. Udeh., et al reported similar posterior segment finding in their study at Enugu, Nigeria [11]. Other studies in Nepal and the USA also had similar results [17,21,22].…”
Section: Discussionsupporting
confidence: 65%
“…In this study, presenting (uncorrected) and best corrected visual acuities were analysed based on WHO classification of visual impairment [15,16]. Our observations in this study is similar to the results reported by Udeh., et al and Ajose., et al in other parts of Nigeria [11,13]. Other developing countries with similar socioeconomic status such as Nepal, Cameroun and Malawi also had similar findings [17][18][19].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Clinical manifestations may include reduced visual acuity, refractive errors, colour vision defects, photophobia, nystagmus, iris transillumination, reduced retinal pigment, foveal hypoplasia and abnormal chiasmal decussation [1,2]. Earlier onset of nystagmus correlates with degree of foveal hypoplasia.…”
mentioning
confidence: 99%